Pengaruh Asupan Tinggi Fruktosa Terhadap Komplikasi Nefropati Diabetik Pada Penderita Diabetes Mellitus - Hanifah Choirunnisa; Waluyo Rudianto; Sutarto (Medula, 2019)
Diabetes mellitus (DM) is a non-communicable disease with a global incidence of 415 million cases in 2015 which has increased 4 times compared to the 1980s in the adult population. The increase in the number of DM in the world in line with the increase in the number of DM in Indonesia in 2018 compared to 2013, which was 1.5%. The increase in the incidence of DM globally causes an increase in various DM complications, one of them is microvascular complications of nephropathy diabetic with an incidence of 20-40%. Increase complication of nephropathy diabetic in people with DM caused by various factors, one of which is an unhealthy lifestyle by consuming a high intake of fructose found in various carbonated soft drinks. Consumption of fructose that is safe for the body no more than 5% of consumption per day. High intake of fructose in carbonated soft drinks increased the greater risk of complications of nephropathy diabetic due to excessive use of ATP in the process of fructose metabolism in the body. The products of fructose metabolism in the body are fructose-1-phosphate and uric acid. Increased fructose-1-phosphate and uric acid will cause hyperglycemia and hyperuricemia which can cause oxidative stress, endothelial dysfunction, and glomerular dysfunction by activating one of the inflammatory mediators inflammatory transcription factors (NF-κB), increasing the production of advanced glycation end products (AGEs) and macrophage activation. Oxidative stress, endothelial dysfunction, and glomerular dysfunction will induce various inflammatory mediators such as cytokines (IL-1, IL-6, IL-18, JAK, STAT and TNF), chemokines (CCL2), and adhesion molecules (ICAM1, VCAM1 ) which causes kidney infiltration of inflammatory cells (monocytes and lymphocytes) which play a role in the pathogenesis of nephropathy diabetic.